Metabolic Imaging of Deep Brain Stimulation in Meige Syndrome - Liu, Jiayu; Li, Lei; Li, Yuan; Wang, Qian; Liu, Ruen; Ding, Hu (Frontiers in Aging Neuroscience, 2022)
Objectives: The subthalamic nucleus (STN) has been shown to be a safe and effective deep brain stimulation (DBS) surgical target for the treatment of Meige syndrome. The aim of this study was to compare changes in brain metabolism before and 6 months after STN-DBS surgery. Methods: Twenty-five patients with primary Meige syndrome underwent motor function assessment, including the Burke–Fahn–Marsden Dystonia Rating Scale movement (BFMDRS-M) and disability subscale (BFMDRS-D) and positron emission tomography with an 18[F]-fluorodeoxyglucose scan before and 6 months after STN-DBS surgery. For the voxelwise metabolic change assessment, the p-value was controlled for multiple comparisons using the familywise error rate. Results: There was a signiﬁcant decrease in BFMDRS-M scores 6 months after STN-DBS, from 10.02±3.99 to 4.00±2.69 (p < 0.001). The BFMDRS disability scores also decreased signiﬁcantly from 4.52±2.90 to 0.64±1.29 (p < 0.001). SPM (statistical parametric mapping) analysis revealed hypermetabolism in the left hemisphere in the occipital lobe, superior parietal gyrus, postcentral gyrus and thalamus and in the right hemisphere in the lentiform nucleus, precuneus and precentral gyrus. In addition, in patients with Meige syndrome, the bilateral inferior temporal gyrus and middle frontal gyrus exhibited glucose hypermetabolism. Conclusions: Abnormal metabolic regions and pathophysiological networks are already known to be involved in Meige syndrome. In this study, we found that metabolism was modified in response to STN-DBS.